Adenosine receptors regulate gap junction coupling of the human cerebral microvascular endothelial cells hCMEC/D3 by Ca2+ influx through cyclic nucleotide-gated channels - Bader, Almke; Hell, Stefan (The journal of physiology, 2017)
Key points Gap junction channels are essential for the formation and regulation of physiological units in tissues by allowing the lateral cell-to-cell diffusion of ions, metabolites and second messengers. Stimulation of the adenosine receptor subtype A2B increases the gap junction coupling in the human blood-brain barrier endothelial cell line hCMEC/D3. Although the increased gap junction coupling is cAMP-dependent, neither the protein kinase A nor the exchange protein directly activated by cAMP were involved in this increase. We found that cAMP activates cyclic nucleotide-gated (CNG) channels and thereby induces a Ca2+ influx, which leads to the increase in gap junction coupling. The report identifies CNG channels as a possible physiological link between adenosine receptors and the regulation of gap junction channels in endothelial cells of the blood-brain barrier. Abstract The human cerebral microvascular endothelial cell line hCMEC/D3 was used to characterize the physiological link between adenosine receptors and the gap junction coupling in endothelial cells of the blood-brain barrier. Expressed adenosine receptor subtypes and connexin (Cx) isoforms were identified by RT-PCR. Scrape loading/dye transfer was used to evaluate the impact of the A2A and A2B adenosine receptor subtype agonist 2-phenylaminoadenosine (2-PAA) on the gap junction coupling. We found that 2-PAA stimulated cAMP synthesis and enhanced gap junction coupling in a concentration-dependent manner. This enhancement was accompanied by an increase in gap junction plaques formed by Cx43. Inhibition of protein kinase A did not affect the 2-PAA-related enhancement of gap junction coupling. In contrast, the cyclic nucleotide-gated (CNG) channel inhibitor l-cis-diltiazem, as well as the chelation of intracellular Ca2+ with BAPTA, or the absence of external Ca2+, suppressed the 2-PAA-related enhancement of gap junction coupling. Moreover, we observed a 2-PAA-dependent activation of CNG channels by a combination of electrophysiology and pharmacology. In conclusion, the stimulation of adenosine receptors in hCMEC/D3 cells induces a Ca2+ influx by opening CNG channels in a cAMP-dependent manner. Ca2+ in turn induces the formation of new gap junction plaques and a consecutive sustained enhancement of gap junction coupling. The report identifies CNG channels as a physiological link that integrates gap junction coupling into the adenosine receptor-dependent signalling of endothelial cells of the blood-brain barrier.
Gesehen am 24.10.2018
Im Titel ist "2+" in Ca2+ hochgestellt